Interplays of mutations in waaA, cmk, and ail contribute to phage resistance in Yersinia pestis - Xiao, Lisheng; Qi, Zhizhen; Song, Kai; Lv, Ruichen; Chen, Rong; Zhao, Haihong; Wu, Hailian; Li, Cunxiang; Xin, Youquan; Jin, Yong; Li, Xiang; Xu, Xiaoqing; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Plague caused by Yersinia pestis remains a public health threat worldwide. Because multidrug-resistant Y. pestis strains have been found in both humans and animals, phage therapy has attracted increasing attention as an alternative strategy against plague. However, phage resistance is a potential drawback of phage therapies, and the mechanism of phage resistance in Y. pestis is yet to be investigated. In this study, we obtained a bacteriophage-resistant strain of Y. pestis (S56) by continuously challenging Y. pestis 614F with the bacteriophage Yep-phi. Genome analysis identified three mutations in strain S56: waaA* (9-bp in-frame deletion 249GTCATCGTG257), cmk* (10-bp frameshift deletion 15CCGGTGATAA24), and ail* (1-bp frameshift deletion A538). WaaA (3-deoxy-D-manno-octulosonic acid transferase) is a key enzyme in lipopolysaccharide biosynthesis. The waaA* mutation leads to decreased phage adsorption because of the failure to synthesize the lipopolysaccharide core. The mutation in cmk (encoding cytidine monophosphate kinase) increased phage resistance, independent of phage adsorption, and caused in vitro growth defects in Y. pestis. The mutation in ail inhibited phage adsorption while restoring the growth of the waaA null mutant and accelerating the growth of the cmk null mutant. Our results confirmed that mutations in the WaaA–Cmk–Ail cascade in Y. pestis contribute to resistance against bacteriophage. Our findings help in understanding the interactions between Y. pestis and its phages.